PENGARUH KOMPENSASI , MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN KONTRAK NON MEDIS DALAM MEMBANGUN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi Empiris Rumah Sakit Umum Daerah Kecamatan Asembagus Kabupaten Situbondo) - Pamungkas, Moh Edy Sulistio; Ediyanto, Ediyanto; Minullah, Minullah (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
Hospitals are important health service facilities that provide care through doctors, nurses, and non-medical personnel. Therefore, hospitals must have high-quality human resources to ensure that the services provided are effective and of high quality. The purpose of this study is to analyze and test the effects of Compensation, Work Motivation, and a Work Environment on the Performance of Non-Medical Contract Hospital Employees in Building Job Satisfaction. This study focuses on the Asembagus District General Hospital in Situbondo Regency. This study is an explanatory research. The population consists of non-medical contract employees other than the leader at Asembagus Hospital. The sampling technique employed was total sampling. Data analysis and hypothesis testing were conducted using Partial Least Squares - Structural Equation Modeling (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application show that: compensation has no significant effect on job satisfaction; work motivation has a significant effect on job satisfaction; work environment has a significant effect on job satisfaction; compensation has no significant effect on performance; work motivation does not have a significant effect on performance; work environment has a significant effect on performance; and job satisfaction has a significant effect on performance. The results of the indirect influence hypothesis test indicate that compensation has a negative and insignificant effect on performance through job satisfaction, work motivation has a significant positive effect on performance through job satisfaction, and work environment has a significant positive effect on performance through job satisfaction.